Anti-cancer activity of guggulsterone by modulating apoptotic markers: a systematic review and meta-analysis - Meenakshi Gupta; Deepti Singh; Shruti Rastogi; Shruti Rastogi; Hifzur R. Siddique; Noura Al-Dayan; Ajaz Ahmad; Mohammad Sikander; Maryam Sarwat (Frontiers Media S.A., 2023)
Background: Guggulsterone (pregna-4,17-diene-3,16-dione; C21H28O2) is an effective phytosterol isolated from the gum resin of the tree Commiphora wightii (Family Burseraceae) and is responsible for many of the properties of guggul. This plant is widely used as traditional medicine in Ayurveda and Unani system of medicine. It exhibits several pharmacological activities, such as anti-inflammatory, analgesic, antibacterial, anti-septic and anticancer. In this article, the activities of Guggulsterone against cancerous cells were determined and summarized.Methods: Using 7 databases (PubMed, PMC, Google Scholar, Science Direct, Scopus, Cochrane and Ctri.gov), the literature search was conducted since conception until June 2021. Extensive literature search yielded 55,280 studies from all the databases. A total of 40 articles were included in the systematic review and of them, 23 articles were included in the meta‐analysis.The cancerous cell lines used in the studies were for pancreatic cancer, hepatocellular carcinoma, head and neck squamous cell carcinoma, cholangiocarcinoma, oesophageal adenocarcinoma, prostrate cancer, colon cancer, breast cancer, gut derived adenocarcinoma, gastric cancer, colorectal cancer, bladder cancer, glioblastoma, histiocytic leukemia, acute myeloid leukemia and non-small cell lung cancer. The reliability of the selected studies was assessed using ToxRTool.Results: Based on this review, guggulsterone significantly affected pancreatic cancer (MiaPaCa-2, Panc-1, PC-Sw, CD18/HPAF, Capan1, PC-3), hepatocellular carcinoma (Hep3B, HepG2, PLC/PRF/5R), head and neck squamous cell carcinoma (SCC4, UM-22b, 1483), cholangiocarcinoma (HuCC-T1, RBE, Sk-ChA-1, Mz-ChA-1) and oesophageal adenocarcinoma (CP-18821, OE19), prostrate cancer (PC-3), colon cancer (HT-29), breast cancer (MCF7/DOX), gut derived adenocarcinoma (Bic-1), gastric cancer (SGC-7901), colorectal cancer (HCT116), bladder cancer (T24, TSGH8301), glioblastoma (A172, U87MG, T98G), histiocytic leukemia (U937), acute myeloid leukemia (HL60, U937) and non-small cell lung cancer (A549, H1975) by inducing apoptotic pathways, inhibiting cell proliferation, and regulating the expression of genes involved in apoptosis. Guggulsterone is known to have therapeutic and preventive effects on various categories of cancers. It can inhibit the progression of tumors and can even reduce their size by inducing apoptosis, exerting anti-angiogenic effects, and modulating various signaling cascades. In vitro studies reveal that Guggulsterone inhibits and suppresses the proliferation of an extensive range of cancer cells by decreasing intrinsic mitochondrial apoptosis, regulating NF-kB/STAT3/β-Catenin/PI3K/Akt/CHOP pathway, modulating the expression of associated genes/proteins, and inhibiting angiogenesis. Furthermore, Guggulsterone reduces the production of inflammatory markers, such as CDX2 and COX-2. The other mechanism of the Guggulsterone activity is the reversal of P-glycoprotein-mediated multidrug resistance. Twenty three studies were selected for meta-analysis following the PRISMA statements. Fixed effect model was used for reporting the odds ratio. The primary endpoint was percentage apoptosis. 11 of 23 studies reported the apoptotic effect at t = 24 h and pooled odds ratio was 3.984 (CI 3.263 to 4.865, p < 0.001). 12 studies used Guggulsterone for t > 24 h and the odds ratio was 11.171 (CI 9.148 to 13.643, 95% CI, p < 0.001). The sub-group analysis based on cancer type, Guggulsterone dose, and treatment effects. Significant alterations in the level of apoptotic markers were reported by Guggulsterone treatment.Conclusion: This study suggested that Guggulsterone has apoptotic effects against various cancer types. Further investigation of its pharmacological activity and mechanism of action should be conducted. In vivo experiments and clinical trials are required to confirm the anticancer activity.